Bio-Briquettes Technology in Power and Heat Generation – A Sustainable Source of Energy - Shahir Liew, Mohd (2010)
Malaysia and Indonesia contributed in excess of 100 million tons of waste generated from the Oil Palm Industry in the form of empty fruit bunch (EFB) and other fibrous waste generated in the extraction of crude palm oil. A technology was developed and patented to recycle the waste from EFB, fronds, palm kernel shells, and mesocarp fibers into useful sustainable and renewable products called bio-briquettes. These wastes has moisture content of 60-70% for EFB and mesocarp fibre, and 34-40% for palm kernel shell, and calorific value of 5.0 - 18.0 Mj/kg. A processing technology was developed to process these low quality biomass fuels into high quality solid bio-briquettes with moisture content in the range 8-12%. Depending on the formulations and the sources of the raw biomass, the final solid bio-briquettes can have calorific values in the range of 18-25 Mj/kg. With calorific values matching that of coals with low moisture content, the bio-briquettes can be used as a heating source and in power generation especially for small renewable energy power plant or in co-generation of large scale power plant. The bio-briquettes yields a carbon content of at least 45 % by weight and is an attractive source of renewable and sustainable material eligible for carbon credit under the Celan Development Mechanism (CDM) scheme. With an estimated margin of production of 45 % or better, the potential revenue from this product is equivalent and competitive to coal currently available in the commodity market for power generation. A higher margin can be obtained if the product is used for domestic heating due to its novelty value. As a contribution to mankind, bio-briquettes are developed from waste which is renewable and sustainable and at the same time provide a source of energy in our quest for alternative energy.